Perancangan Dokumen Hazard Identification Risk Assessment Risk Control (HIRARC) Pada Perusahaan Furniture: Studi Kasus - Lydia Natalia Halim; Togar Wiliater Soaloon Panjaitan (Jurnal Titra, 2016)
A good implementation of occupational safety and health management system could improve the protection effectiveness of safety and worker’s health. This research has a purposes which is to plan a document of Hazard Identification, Risk Assesment and Risk Control (HIRARC) based on OHSAS 18001:2007. These HIRARC documents are made to fulfill consument requirements and reduce employee medical expenses. The results shows 28% of activities considerate to be low risk, 55% of activities considerate to be moderate risk, and 17% of activities considerate to be high risk. Total HIRARC documents are 45 documents. Activities in process area, preparation, and finishing area are considered to be high risk. The most hazardous area at warehouse is paint chemical warehouse. Risk controlling is being done by elimination, substitution, engineering, and administration methodes. The top management must committed to implement occupatinal health and safety policies properly on the company, so the cost required to handle workplace accidents can also be reduced.